Comparative morphology of larval Camiarinae (Coleoptera: Leiodidae)Part I. Genus Paragyrtodes Szymczakowski 1966 - Kilian, Aleksandra (Zootaxa, 2007)
The first, second and third larval instars of the Australian genus Paragyrtodes Szymczakowski, 1966 are described. Among three described species, larvae of two, P. candens Szymczakowski, 1966 and P. modestus Szymczakowski, 1966, are redescribed in detail, illustrated, photographed and measured. The chaetotaxy and porotaxy are given and their system is discussed. Morphological and chaetotaxic characters distinguishing mature larvae of two species of Paragyrtodes are provided; differences among mature larvae of the genera Agyrtodes Portevin, 1907 and Paragyrtodes are summarized. Pretergal glands, their glandular function, and tergal pores are documented in the family Leiodidae for the the first time. The problem of the identity of the larval glands in the family Leiodidae and superfamily Staphylinoidea is discussed. Data on presence, number and arrangement of the tergal and pretergal glands for all known larvae of Leiodidae and some representatives of Staphylinidae and Hydraenidae are gathered.